PROFITABILITY: CAN IT INCREASE FIXED ASSETS INVESTMENT? - Wijana, I Made Dauh; Adnyana, I Made Dwi (The journal of contemporary issues in business and government, 2021)
Profitability is not only used to measure the company's ability to generate profits, but also to determine the effectiveness of the company in managing its resources. A company is said to be good if it has a level of profitability that is able to reflect the sustainability of the company. This study aims to test and obtain empirical evidence regarding the role of fixed asset investment in moderating the effect of working capital efficiency, sales growth, company size, and cash turnover on profitability in food and beverage companies listed on the Indonesia Stock Exchange 2016-2018 The research population is all manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. The sample in this study were 15 manufacturing companies which were determined based on purposive sampling technique. The analysis technique used is Moderated Analysis Regression. The results showed that working capital efficiency and firm size had a positive effect on profitability, cash turnover and sales growth had no effect on profitability, fixed asset investment was able to moderate the effect of sales growth and company size on profitability, but fixed asset investment was unable to moderate the effect of working capital efficiency. and cash turnover on profitability.